Predominant monomorphism of the RIT2 and GPM6B exceptionally long GA blocks in human and enriched divergent alleles in the disease compartment - Khamse, S.; Arabfard, M.; Salesi, M.; Behmard, E.; Jafarian, Z.; Afshar, H.; Khazaei, M.; Ohadi, M. (Genetica, 2022)
Across human protein-coding genes, the human neuron-specific genes, RIT2 and GPM6B , contain the two longest GA short tandem repeats (STRs) of 11 and 9-repeats, respectively, the length ranges of which are functional, and result in gene expression alteration. Here we sequenced the RIT2 and GPM6B STRs in 600 human subjects, consisting of late-onset neurocognitive disorder (n = 200), multiple sclerosis (n = 200), and controls (n = 200). Furthermore, we selected two large human databases, including the general-population-based gnomAD ( https://gnomad.broadinstitute.org ) and a mainly disease-phenotype-archiving database, TOPMed ( https://www.nhlbiwgs.org ), to compare allele frequencies in the general populations vs. the disease compartment. The RIT2 and GPM6B GA-repeats were monomorphic in the human subjects studied, at lengths of 11 and 9-repeats, respectively, and were predominantly human-specific in formula. Exception included a 9/11 genotype of the RIT2 GA-STR in an isolate case of female multiple sclerosis. Exceedingly rare alleles of the two GA repeats were significantly enriched in TOPMed vs. the gnomAD. We report prime instances of predominant monomorphism for specific lengths of STRs in human, and possible enrichment of rare divergent alleles in the disease phenotype compartment. While STRs are most attended because of their high polymorphic nature, STR monomorphism is an underappreciated feature, which may have a link with natural selection and disease.